(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the structural paradigms, receptive aesthetics and reception of a work of art. It is emphasized that literary relations are important in ensuring the development of literature, while attention is paid to the activities of two main factors in the process of “Literary Relations” - the receiving and receiving parties. The issue of influence and interpretation in Uzbek literary criticism is illuminated using the example of the work of Albert Camus. Also, the concept of “national reception” was included as an innovation in the classification developed by the German researcher Reinard Dohl.